Self-sustaining slab dynamics of the underthrusting Indian lithosphere shaping the giant Himalayan Orocline - Chunsen Li; Hengcheng Ying; Xiao Xu; Xiaoyu Guo; Xiaofei Tong; Lingyan Li; Hongcheng Shi; Zizhao Yuan; Yanqi Lin; Xinglang Yin; Huolong Xu; Xiaodong Lan (Earth-Science Reviews, 2026)

Alnustone ameliorates obesity and polycystic ovary syndrome by remodeling adipose metabolism via AMPK signaling - Yiming Qin; Shourui Hu; Yanqi Xu; Zongxuan Lin; Xiaofan Liang; Yue Liu; Yuxuan Li; Chunxuan Geng; Xiangyan Chen; Xizi Feng; Zi-Jiang Chen; Han Zhao; et al. (Science China Life Sciences, 2026)

Naringenin-loaded nanoparticles based on sodium caseinate and carboxymethyl chitosan for filled starch gels: Characterization, texture, stability, bioactivity, and digestion - Peijian Cai; Yingying Cao; Yifan Zhang; Yanqi Lin; Wenwen Feng; Yi Liu; Zhaozhi Zeng; Fansheng Kong (Food Bioscience, 2026)

Epidemiology of esophageal cancer in Xiamen, China, 2011–2020: trends in incidence, mortality, and survival from a population-based registry study - Haixia Zhang; Youlan Chen; Yilan Lin; Jiahuang Chi; Yanqi Lan; Qun Lou; Ahua Wu; Zhinan Guo (Cancer Causes & Control, 2026)

Mariana trench-derived fungal polysaccharide AVP214–1 inhibits Singapore grouper iridovirus infection in vitro and in vivo - Xinyu Liao; Gaoqi Yu; Xiaohui Zheng; Yanqi Zhao; Siting Wu; Weifu Mo; Yijie Lin; Xiaoyong Zhang; Zhuang Han; Qiwei Qin; Jingguang Wei (Aquaculture, 2026)

Diatomaceous bio-silicon as a sustainable alternative to mineral silicon fertilizers: impacts on rice yield, soilfertility, and heavy metal dynamics - Yanqi Guo; Shengnan Ouyang; Junquan Chen; Zhi Lin; Chao Xiao; Dong Liu; Guangjie Chen; Qin Zhang (Plant and Soil, 2026)

Evaluating technical soil derived from lithium mica residue: Integrating soil quality and life cycle assessment for functional performance and environmental sustainability - Yanqi Li; Zi Guo; Xinyan Lv; Xin Liao; Guilan Duan; Liping Fang; Xiaoliang Li; Xiao Tan; Aijun Lin (Journal of Cleaner Production, 2026)

Comparative study of machine learning and deep learning in predicting the shear strength of marine sand and polymer layer interfaces interface under marine temperature effects - Zhiming Chao; Yanqi Liu; Dongbo Jiang; Hongbo Du; Wei You; Xianhui Feng; Jie Lin; Peng Cui; Zejin Wang (Frontiers in Marine Science, 2025)
In marine engineering, polymer layers are anti-seepage barrier materials. The mechanical interaction between marine sand and polymer layer significantly affects overall structural stability. In this study, direct shear tests at different temperatures in the marine environment are simulated to evaluate the shear behavior of marine sand and polymer layer interface, and a database is developed. Based on the experimental data, the study employs the Back propagation Neural Network (BPNN), Genetic Algorithm and Particle Swarm Optimization BPNN, and convolutional neural network (CNN) models, which are trained and tested. The findings show that the CNN algorithm significantly outperforms other models in terms of prediction accuracy and efficiency. Sensitivity analysis shows that temperature, shear displacement, normal stress, and particle size have influence on interfacial shear strength, and the impact of normal stress is the greatest. In addition, an empirical formulation is proposed to provide tools for those without machine learning. Based on the research results, the deep learning CNN model developed in the study can accurately predict the shear strength of the interface between marine sand and the polymer layer, which provides an effective tool for the design and optimization of marine engineering.

Synergistic enhancement of thermoelectric performance in SnTe via Bi and Ge Co-doping - Minwen Yang; Jingyi Lyu; Junyu Lin; Yanqi Huang; Zehao Lin; Rui Zhang; Jing Shuai; Yanglong Hou (Chemical Engineering Journal, 2025)

The Interplay Between Climate Warming Driven by Greenhouse Gas Emissions and the Ecotoxicological Effects of Microplastics: Insights From a Meta‐Analysis - Xinyan Lv; Aijun Lin; Xuedan Cui; Yanqi Li; Zi Guo; Xiao Tan; Guilan Duan (Global Change Biology, 2025)
An increasing number of studies have revealed the interconnections and interactions between global warming and microplastics. However, research in this field is still in its early stages, with fragmented content and inconsistent conclusions. Therefore, this paper adopts a meta‐analysis method to summarize and analyze the relevant literature in this area. After screening, a total of 39 research papers and 730 data points related to the interactions between global warming and microplastic pollution were obtained. The research results indicate that, on one hand, soil microplastic pollution significantly increases greenhouse gas CO 2 emissions by 140.20%, N 2 O emissions by 195.27%, and Global Warming Potential by 172.10%, thereby exacerbating global warming. By introducing explanatory variables for analysis, it was found that microplastic type, soil type, and soil dissolved organic carbon are important influencing factors. On the other hand, the study also explains that the rise in water temperature due to global warming amplifies the biological toxicity effects of microplastics, leading to oxidative damage and poisoning in aquatic animals. The bidirectional interaction mechanism between microplastic pollution and global warming may form a vicious cycle, further increasing the vulnerability of ecosystems. This study provides a theoretical basis and research direction for addressing the dual threats of microplastic pollution and global warming.

Reduction-stabilization characteristics, long-term stability and biotoxicity evaluation of Fe(II)/Al layered double hydroxides on Cr(VI) in contaminated soil - Xiao Tan; Qi Liu; YanQi Li; Xinyan Lv; Zi Guo; Guilan Duan; Aijun Lin (Environmental Pollution, 2025)

Crustal-scale architecture and origin of the Haiyuan Arcuate Tectonic Belt, NE Tibet - Zizhao Yuan; Yanqi Lin; Xiao Xu; Huilin Li; Xiaoyu Guo; Chunsen Li; Xiaofei Tong (Tectonophysics, 2024)

Bird detection and overall bird situational awareness at airports - Hongxuan Fu; Chunyi Wang; Nihed Benani; Mingqi Zhang; Jian Lin Chen; Yanqi Gong; Xunqiang Mo; Jinjing Gao; Guozhu Mao (Ornithology Research, 2024)

OsPRMT6a-mediated arginine methylation of OsJAZ1 regulates jasmonate signaling and spikelet development in rice - Kun Dong; Fuqing Wu; Siqi Cheng; Shuai Li; Feng Zhang; Xinxin Xing; Xin Jin; Sheng Luo; Miao Feng; Rong Miao; Yanqi Chang; Shuang Zhang; et al. (Molecular Plant, 2024)

Heavy metal migration dynamics and solid-liquid distribution strategy in abandoned tailing soils - Bohan Wu; Quan Wan; Xiao Li; Shukun Lin; Yanqi Jiang; Xu Yang; Jingjing Li; Qingqi Lin; Jean Louis Morel; Rongliang Qiu (Journal of Hazardous Materials, 2024)

DDT and titanium dioxide nanoparticle coexposure induced neurobehavioral deficits in zebrafish - Jian Lin; Yanqi Lou; Zhenkai Sun; Dongliang Pan; Lei Lei; Yang Song; Changjiang Huang; Jiangfei Chen (Neurotoxicology and Teratology, 2024)

Association of greenness surrounding school with aggression among adolescents: A multi-site study in China - Yi Zhang; Yanqi Li; Xinyi Xie; Xiaoyi Lin; Mengxin Huang; Huihang Fu; Weiju Zhou; John S. Ji; Yizhen Yu; Jie Tang (Environmental Research, 2023)

Pexidartinib hydrochloride exposure induces developmental toxicity and immunotoxicity in zebrafish embryos via activation of Wnt signaling - Fasheng Liu; Hongmei Hu; Guilan Chen; Yanqi Lin; Wei Li; Ziyi Liu; Chao Chen; Xue Li; Sujie Sun; Li Zhang; Dou Yang; Kangyu Liu; et al. (Fish & Shellfish Immunology, 2023)

Neonicotinoids residues in cow milk and health risks to the Chinese general population - Xin Wei; Yanan Pan; Zixiong Tang; Qingqi Lin; Yanqi Jiang; Jingyuan Chen; Weixuan Xian; Renli Yin; Adela Jing Li; Rongliang Qiu (Journal of Hazardous Materials, 2023)